2020
DOI: 10.1111/phn.12759
|View full text |Cite
|
Sign up to set email alerts
|

Promoting dementia awareness in African‐American faith communities

Abstract: Introduction Alzheimer's disease and other dementia‐related disorders are affecting the African‐American community at alarming rates. African‐American churches have traditionally been places of refuge where families go for support. However, many churches lack programs or resources to support families affected by dementia. In response, a nurse‐led interdisciplinary collaborative partnered with churches to promote dementia awareness through education. Purpose The purpose of this analysis was to (a) describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 23 publications
1
31
0
Order By: Relevance
“…The churches varied in Christian denomination and included United Methodist ( n = 1), Pan African Orthodox Christian ( n = 1), African Methodist Episcopal ( n = 1), Catholic ( n = 1), and non-denominational ( n = 2) congregations. The workshops were facilitated by Faith Village Connections (FVC), an interdisciplinary collaborative developed by the primary author and comprised of predominantly African American women, to address gaps in the lack of resources and awareness about dementia in African American faith communities (Epps, Alexander, et al, 2020). Current research and resources from aging support organizations (i.e., Alzheimer’s Association, AARP, The Eden Alternative, and SageNavigator) guided the curriculum content.…”
Section: Methodsmentioning
confidence: 99%
“…The churches varied in Christian denomination and included United Methodist ( n = 1), Pan African Orthodox Christian ( n = 1), African Methodist Episcopal ( n = 1), Catholic ( n = 1), and non-denominational ( n = 2) congregations. The workshops were facilitated by Faith Village Connections (FVC), an interdisciplinary collaborative developed by the primary author and comprised of predominantly African American women, to address gaps in the lack of resources and awareness about dementia in African American faith communities (Epps, Alexander, et al, 2020). Current research and resources from aging support organizations (i.e., Alzheimer’s Association, AARP, The Eden Alternative, and SageNavigator) guided the curriculum content.…”
Section: Methodsmentioning
confidence: 99%
“…research but may also result in more culturally appropriate and effective services. [420][421][422][423][424][425][426][427][428][429][430][431][432] In addition, a greater understanding is needed of how multiple chronic diseases (multimorbidity) intersect with dementia among Black people, indigenous peoples and people of color. 433…”
Section: Race/ethnicity and Dementia Caregivingmentioning
confidence: 99%
“…This hinders the progress of all Alzheimer's disease caregiving research, and, by extension, if these individuals continue to lack representation in Alzheimer's research, they will not receive the benefits of prevention, treatment or care innovations 413 . Establishing stronger relationships with existing organizations and resources in Black communities, indigenous communities and communities of color offers the potential of research‐based partnerships that not only enhance representation in Alzheimer's disease research but may also result in more culturally appropriate and effective services 420–432 . In addition, a greater understanding is needed of how multiple chronic diseases (multimorbidity) intersect with dementia among Black people, indigenous peoples and people of color 433 …”
Section: Caregivingmentioning
confidence: 99%
“…Studies were also conducted in culturally sensitive settings. For example, one study held educational sessions at Black/African American churches as these are pillars of trust for African Americans in the Atlanta area of the United States 14 . In addition, a study observed religious customs in refreshments, music, venue, and intervention timing 10 …”
Section: Resultsmentioning
confidence: 99%
“…Black older adults were also found to have a high level of religious participation 51 . Therefore, when promoting dementia knowledge in this population, barriers were addressed via the use of low‐literacy text messages rather than via app that requires Internet access 27 and recruitment via faith‐based organizations 14 . Among all studies, three used YouTube as an intervention delivery mode, and all reported an increase in video engagement over time.…”
Section: Discussionmentioning
confidence: 99%